The Role and Functions of Social Media in Modern Society. Is social Media Worthwile for Local Media? - Murinska Gaile, Sandra (Žurnalistikos tyrimai, 2013)
[straipsnis ir santrauka anglų kalba] The purpose of this article is to explore if the social media are worthwile for the local media. Currently, all types of the mass media under the influence of the social media experience changes caused by the technologies in the processes of obtaining and consuming the information. The article reveals the representation of the local media of Latvia in the electronic environment, mainly in social networks. The use of social media is analysed in the context of theory of innovations diffusion, considering social media as a novelty in the local media space. The empirical research has revealed that the local media do not implement all the advantages which are possible to develop within the digital environment. First of all, at the level of interactivity, the media do not offer the material which may provoke a comment or a feedback from the user. Secondly, the personalization allows seeing in detail whether the local media were able to adopt innovation and to inform the audience about it or not. It means that a particular interest is necessary to adopt an innovation. Thirdly, the potential convergence of the Internet and the traditional media mostly is seen at the level of images and text. The social networks for local media in this case use the most necessary opportunities; wider activities are performed in the traditional environment.